2020
DOI: 10.3390/en13020322
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and Application for Hydraulic Electric Hybrid Vehicle

Abstract: Targeting the application of medium and heavy vehicles, a hydraulic electric hybrid vehicle (HEHV) was designed, and its energy management control strategy is discussed in this paper. Matlab/Simulink was applied to establish the pure electric vehicle and HEHV models, and backward simulation was adopted for the simulation, to get the variation of torque and battery state of charge (SOC) through New York City Cycle of the US Environmental Protection Agency (EPA NYCC). Based on the simulation, the energy manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…Hwang et al reported on "Optimization and Application for Hydraulic Electric Hybrid Vehicle" [1]. In this research, the rule-based control strategy was implemented as the energy distribution management strategy first, and then the genetic algorithm was utilized to conduct global optimization strategy analysis.…”
Section: The Topic Of Energies and Its Applicationsmentioning
confidence: 99%
“…Hwang et al reported on "Optimization and Application for Hydraulic Electric Hybrid Vehicle" [1]. In this research, the rule-based control strategy was implemented as the energy distribution management strategy first, and then the genetic algorithm was utilized to conduct global optimization strategy analysis.…”
Section: The Topic Of Energies and Its Applicationsmentioning
confidence: 99%
“…Among them, the rule-based EMS, which is easy to implement and has good robustness as well as low development cost, is the first control strategy applied to hybrid electric vehicles. [2][3][4] It is mainly based on engineering experience or optimization algorithm to make a series of rules for determining the trigger threshold value of different working paths. In practice, the current operating mode should be selected based on the data collected in real-time.…”
Section: Introductionmentioning
confidence: 99%
“…Rule-based strategies are generally known as the summary of engineers' long-term working experience. Typical representatives of these schemes include the thermostat method, power following method, engine optimal working point strategy and the fuzzy method [4]- [6]. Further investigations revealed that this method has superior characteristics, including reasonable real-time performance, simple and effective algorithm and simple implementation.…”
Section: Introductionmentioning
confidence: 99%